“I'd like five of them”: the racialization and commodification of internationally recruited nurses in the German healthcare sector - Tanja Gangarova; Johanna Kechout; Hans Vogt (Frontiers in Sociology)
While research in North American and Australian contexts demonstrates how encountering racism in healthcare is burdensome, the impact of racism on healthcare interactions in Europe, and particularly in Germany, remains underexplored. This paper draws on a study that examines the intersections of interpersonal, institutional, and structural racism in the professional experiences of internationally recruited nurses and integration managers in Germany who self-identify as “affected by racism.” The aim is to deepen our understanding of the forms, dynamics, and effects of racism within a healthcare sector increasingly shaped by economization. Employing an exploratory qualitative research design, the study is based on 21 semi-structured interviews and 10 participant diaries. Data analysis followed an iterative process, integrating inductive and deductive approaches within a framework of qualitative content analysis and emphasizing study participants' perspectives. The analytical framework developed in this paper addresses the intertwined processes of racialization and commodification and contributes to an empirically grounded conceptual understanding of recruited nurses' experiences of racism within nursing settings. This methodological approach reveals the subtle mechanisms through which racial inequalities are (re)produced and the ways that recruited labor is commodified in the German healthcare context. Findings suggest that these dynamics not only harm internationally recruited nurses, but also contribute to the invisibilization of racism within the sector. Furthermore, the analysis provides a nuanced account of racialized labor relations in transnational healthcare work and the global dynamics of care drain. In doing so, the paper identifies critical areas for institutional change and transformation, and it underscores the broader power structures that must be addressed in order to advance equity and justice in nursing.